National Unemployed Workers' Movement Collection Card, late 1930s
1939 1918-1939 "National Unemployed Workers' Movement Collection Card, late 1930s" [T0141.jpg], 1930s The National Unemployed Workers Movement (NUWM) was formed at a meeting in London of representatives of local unemployed committees on 15 April 1921 - 'Black Friday' which saw the collapse of the Triple Alliance. The leader of the NUWM was Wal Harrington (1896-1966) a tool maker and member of the Communist Party. Its first activity was to organise a march from London to the Labour Party conference in Brighton in 1921. Over the next 15 years, the NUWM organised a number of Hunger Marches across the country. After the 1932 march the NUWM leadership including Harrington and Tom Mann were imprisoned. Between 1923-26, there was a joint TUC-NUWM committee but thereafter the two organisations were mutually hostile and the TUC set up its own network of unemployed associations in the late 1920s. By February 1933, the NUWM claimed 100,000 members in 349 branches. It was strongest in mining areas, particularly Scotland and South Wales. It was finally dissolved in February 1946.